Modeling the Residence Time Distribution of Integrated Continuous Bioprocesses. Issue 8 (11th May 2020) - Sencar, Jure; Hammerschmidt, Nikolaus; Jungbauer, Alois
Abstract: In response to the biopharmaceutical industry advancing from traditional batch operation to continuous operation, the Food and Drug Administration (FDA) has published a draft for continuous integrated biomanufacturing. This draft outlines the most important rules for establishing continuous integration. One of these rules is a thorough understanding of mass flows in the process. A computer simulation framework is developed for modeling the residence time distribution (RTD) of integrated continuous downstream processes based on a unit‐by‐unit modeling approach in which unit operations are simulated one‐by‐one across the entire processing time, and then combined into an integrated RTD model. The framework allows for easy addition or replacement of new unit operations, as well as quick adjustment of process parameters during evaluation of the RTD model. With this RTD model, the start‐up phase to reach steady state can be accelerated, the effects of process disturbances at any stage of the process can be calculated, and virtual tracking of a section of the inlet material throughout the process is possible. A hypothetical biomanufacturing process for an antibody was chosen for showcasing the RTD modeling approach. Abstract : A thorough understanding of mass flows in the process is required by the Food and Drug Administration (FDA) in their draft on guidelines for continuous integrated biomanufacturing. A framework is created for modeling residence time distributions (RTD). The framework can produce RTD models based on available data about such integrated processes and is publicly available under the open source license.